PERBANDINGAN TUTURAN DEKLARATIF BERMAKNA IMPERATIF DALAM NOVEL TEBUSAN DARAH DENGAN HEMPASAN GELOMBANG - Juang Rizki Faznur; Hasnah Faizah. AR; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research discusses about comparison declarative speech meaningful imperative in novel Tebusan Darah with novel Hempasan gelombang. This research used by qualitative approach and descriptive method that aims to describe declarative speeches in novel Tebusan darah with Novel Hempasan gelombang and their comparison. In this research, researcher used documentation collection data techniques, and then classified by their form or type of declarative speech meaningful imperative. The results of this research is the researcher have found form or type declarative speech meaningful imperative contained in both novel such declarative speech meaningful imperative errands, invitiation, solicitations, invite, prohibition, and demand.Keywords : Comparison of Declarative Speech, Meaningful Imperative, Novel Tebusan Darah,Novel Hempasan Gelombang